Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja Pegawai Di RS Prima Husada Kota Sengkang - Arafah, Muhammad Zulfikar; Hasbiah, Siti; Akbar, Abdi; Kurniawan, Agung Widhi; Burhanuddin (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of leadership style on job satisfaction of employees at Prima Husada Sengkang Hospital, the subjects in this study were 52 employees working at Prima Husada Hospital. This research is included in quantitative research and quantitative analysis to test the research hypothesis using the IMB SPSS version 25 software. The results of this study indicate that leadership style has a positive and significant effect on job satisfaction. This is evidenced by the calculated t value of -11.576 where <t table (1.67655) and a significance value of 0.000 <0.05. The results of the study show that leadership style has a positive and significant effect on job satisfaction. This is evidenced by the t value of 11.576 < t table (1.67655) and a significance value of 0.000 > 0.05. The results of the study show that leadership style has a partial effect on job satisfaction. This is evidenced by the calculated F value of 134.003 > 3.10 and a significance value of 0.000 <0.05.